SETTLEMENT OF DEFAMATION CRIMINAL CASES THROUGH SOCIAL MEDIA WITH A RESTORATIVE JUSTICE APPROACH - Indah Satria; I Gede Agung (Faculty of Law, Tanjungpura University, 2023)
AbstractLiterally, Restorative Justice is the restoration of justice, but more clearly Restorative Justice is an approach that focuses on conditions for the creation of justice and balance for the perpetrators and the victims themselves. Meanwhile, defamation is an act of attacking someone's honor or good name by accusingsomething that is clearly meant so that it is publicly known. This study aims to find out what Restorative Justice is, how cases of defamation are resolved with this approach, and what are the factors the perpetrators commit criminal acts of defamation in the study of decisions examined. The factors causing the occurrence of defamation crimes through social media in the city of Bandar Lampung are heartache factors due to events experienced by perpetrators of defamation through social media, there are also political factors, as well as factors of lack of legal awareness by perpetrators of defamation crimes through social media. AbstrakSecara harfiah Keadilan Restoraif adalah pemulihan keadilan, tetapi secara lebih jelas Keadilan Restoratif adalah suatu pendekatan yang menitik beratkan pada kondisi terciptanya keadilan dan keseimbangan bagi pelaku serta korbannya sendiri. Sedangkan pencemaran nama baik adalah perbuatan menyerang kehormatan atau nama baik seseorang dengan menuduhkan sesuatu hal yang maksudnya terang supaya hal itu diketahui umum. Penelitian ini bertujuan untuk mengetahui apa itu Keadilan Restoratif atau Restorative Justice, bagaimana penyelesian perkara pencemaran nama baik dengan pendekatan tersebut, dan apa faktor-faktor pelaku melakukan tindak pidana pencemaran nama baik dalam studi putusan yang di teliti. Adapun faktor penyebab terjadinya kejahatan pencemaran nama baik melalui media sosial di kota Bandar Lampung adalah faktor sakit hati akibat adanya peristiwa yang dialami pelaku kejatahan pencemaran nama baik melalui media sosial, juga ada pula faktor politik, serta faktor kurangnya kesadaran hukum oleh pelaku kejahatan pencemaran nama baik melalui media sosial.